Pengaruh Faktor Hygiene Dan Motivasi Terhadap Kepuasan Kerja Karyawan Pada CV Sayap Mas Nusantara Kabupaten Malang - Maulana, Muhammad Rizqi; Djaelani, Abdul Kodir; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research purposes to examine the impact of hygiene factors and motivation elements on employee job satisfaction at CV Sayap Mas Nusantara in Malang Regency. This research employs quantitative research methods. The population of this study was 1500 employees from CV Sayap Mas Sukosari in Gondanglegi, Malang Regency. Meanwhile, the sample applied the Slovin formula on the calculated findings of 94 samples. The data used are secondary and primary data collected through questionnaire approaches. The data analysis approach employed is instrument testing: validity, reliability, normality, multiple linear regression analysis, hypothesis testing (simultaneous, partial, and coefficient of determination). The study's findings demonstrate that both the Hygiene and Motivation factors have a substantial impact on employee job satisfaction at CV Sayap Mas Nusantara Malang Regency. Part of the findings revealed that the hygiene element had no significant effect on employee job satisfaction, whereas work motivation did..Keywords : Hygiene Factors, Work Motivation, Job Satisfaction